Candid love: The crux of Mtaphysical poetry (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Literally the word ‘Metaphysical’ is a blending of two different words ‘meta’ meaning beyond and ‘physical’ meaning the earthly world or the material world. The very term ‘Metaphysical’ was first coined by the 18th century English poet, playwright, essayist, and critic Dr. Samuel Johnson (1709-1784) in his book ‘Lives of the Most Eminent English Poets (1779-1781)’Dr. Johnson Writing about Abraham Cowley made a gross generalization about the English poets of the age writing:‘About the beginning of the 17th century appeared a race of writers that may be termed as Metaphysical poets.’[1]He further wrote that these poets were scholars and tried to display their knowledge in their poems. They ransacked nature and art for ‘illustrations, comparisons and allusions’ and created conceits in which the most ‘heterogeneous ideas’ are hitch by violence composed. They were more concerned with the admirability than the understandability of their conceits. He quotes from the different poets of the time to substantiate it:‘By every wind that comes this way, send me, at least a sigh or two’(Cowley)or, the medicinal knowledge conveyed by John Donne in “To The Countless of Bedford”:“In everything there naturally grows, A balsamum to keep it fresh and new.” Dr. Johnson used the term ‘metaphysical’ as a piece of literary slung.